Progressive heterosis in genetically defined tetraploid maize. (20th August 2019) - Washburn, Jacob D.; McElfresh, Mitchell J.; Birchler, James A.
Abstract: Progressive heterosis, i.e., the additional hybrid vigor in double-cross tetraploid hybrids not found in their single-cross tetraploid parents, has been documented in a number of species including alfalfa, potato, and maize. In this study, four artificially induced maize tetraploids, directly derived from standard inbred lines, were crossed in pairs to create two single-cross hybrids. These hybrids were then crossed to create double-cross hybrids containing genetic material from all four original lines. Replicated field-based phenotyping of the materials over four years indicated a strong progressive heterosis phenotype in tetraploids but not in their diploid counterparts. In particular, the above ground dry weight phenotype of double-cross tetraploid hybrids was on average 34% and 56% heavier than that of the single-cross tetraploid hybrids and the double-cross diploid counterparts, respectively. Additionally, whole-genome resequencing of the original inbred lines and further analysis of these data did not show the expected spectrum of alleles to explain tetraploid progressive heterosis under the complementation of complete recessive model. These results underscore the reality of the progressive heterosis phenotype, its potential utility for increasing crop biomass production, and the need for exploring alternative hypothesis to explain it at a molecular level.